A Study on the Spatio-Temporal Land-Use Changes and Ecological Response of the Dongting Lake Catchment - Nan Yang (MDPI AG, 2021)
Catchments support the survival and development of humans in a region and investigating the mechanism of land-use changes and ecological responses in catchments is of great significance for improving watershed ecological service functions. Taking the Dongting Lake catchment as the study area, this study used spatial analysis, an ecosystem service value (ESV)-equivalent factor method, grid method, and other spatial analysis methods to explore land-use changes and the corresponding ecological service value response from 1990 to 2015, to provide an important theoretical reference for ecological service management, regional planning and ecological service function improvement in the Dongting Lake Basin. Our findings are as follows: (1) apart from a trend of notable expansion in construction land, the land-use types in the Dongting Lake catchment did not change significantly. (2) Grassland had the fastest transfer-out rate; forest land were cultivated land comparably transferred to each other with a larger area, where both were simultaneously and continuously transferred out as construction land; water areas, wetlands, and construction land were all transferred in, where construction land had the fastest transfer rate. (3) The total ESV of the watershed first increased and then decreased, but the overall change was small; spatially, the wetlands and water areas had a higher ESV, whereas construction land and cultivated land had lower ESVs. (4) Soil protection, gas exchange, climate regulation, biodiversity, and water conservation are always the main ecosystem service functions of a catchment, where the service function of the catchment ecosystem is greater than the productive function. The increase in construction land was the main factor for the increased differences between the spatial distributions of the soil, raw materials, biodiversity protection, and gas exchange.